Compras Governamentais nos Municípios do Estado de Mato Grosso do Sul: Proposta de um Roteiro Prático para as Licitações Eletrônicas, com Base na Lei Nº 14.133/2021 - Martins, Cristiane Pereira dos Santos (2023)
It is through public procurement that the State employs a significant portion of its revenues, which is why the themes "bids" and "public contracts" are present in all public organizations, regardless of the sphere of power and the federative entity. Several laws regulate public procurement. The last, Law No. 14,133 of April 1, 2021, among the various changes introduced, indicates the preference for bidding in electronic form and the production of digital acts, which requires the public managers responsible for the processing of purchases, the gathering of efforts and investments to meet these new demands. The general objective of this research is, based on the legislative change and the challenges to be faced by the municipalities of Mato Grosso, to propose a work script for the electronic processing of public purchases. The methodology used was bibliographic and documentary research, as well as the field survey about the work processes and personnel of the municipalities. The result of the study demonstrates that, in addition to the predilection of the sample for bidding in the face-to-face form, the need for procedural adjustments that enable compliance with the new Law is urgent.